Principles of laparoscopic surgery. Issue 3 (March 2020) - Limb, Christopher; Rockall, Timothy
Abstract: Laparoscopic surgery is currently established as the primary modality for many procedures. In has been associated with a number of benefits over traditional open surgery, including reduced pain, shorter hospital stay and quicker return to work. Despite this, significant operative challenges and the potential for life-threatening complications exist. Surgeons must understand the specialist equipment that is required, along with how to troubleshoot common issues. Furthermore, an appreciation of the distinctive surgical techniques and technical challenges is critical in limiting the risk of significant complications. Through this article we discuss these topics in the context of the current literature, aiming to recognize common pitfalls that all surgeons should make a conscious effort to avoid. We will describe those patient groups, specifically obesity, pregnancy, elderly and bowel obstruction, in whom additional caution must be maintained. Finally, we will consider these principles in the context of the wider field of minimally invasive surgery, to include robotics, single incision, transanal microsurgery (TAMIS) and transanal total mesorectal excision (TaTME). Although the landscape of minimally invasive surgery is constantly evolving, a robust understanding of the underlying principles is essential for all surgeons.